DNA‐Templated Synthesis of Perylenediimide Stacks Utilizing Abasic Sites as Binding Pockets and Reactive Sites. (14th October 2016) - Takada, Tadao; Ido, Misa; Ashida, Akane; Nakamura, Mitsunobu; Yamana, Kazushige
Abstract: DNA is considered to be a promising biomolecule as a template and scaffold for arranging and organizing functional molecules on the nanoscale. The construction and evaluation of DNAs containing multiple functional molecules that are useful for optoelectronic devices and sensors has been studied. In this paper we report the efficient incorporation of perylenediimide (PDI) units into DNA by using abasic sites both as binding sites and as reactive sites and the construction of PDI stacks within the DNA structure, accomplished through the preorganization of the PDI units in the hydrophobic pocket within the DNA. Our approach could become a valuable method for construction of DNA/chromophore hybrid structures potentially useful for the design of DNA‐based devices and biosensors. Abstract : DNA/chromophore hybrid structures : Efficient reactions between amino‐ perylenediimide (aPDI) dyes and DNA duplexes containing abasic nucleosides are described. The abasic sites created in the DNA serve as binding pockets and reactive sites, thus affording a useful method for the construction of PDI stacks within the DNA.